Proceedings of the International Conference on Business, Economic, Social Science and Humanities (ICOBEST 2018) 2018
DOI: 10.2991/icobest-18.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Workload and Competence on Employee Performance in PT X Finance

Abstract: The purpose of this research was to determine the effect of workload and competence on employee performance. This research was conducted at PT X Finance using quantitative sample method is take 70 respondents. Measurement data was done by distributing questionnaires using 5-point Likert scale. The analytical technique used is using SmartPLS 3 software. From the results of the test-t show the value t workload 10.178 > 1.996 and value t 3.996 > 1.996, competence and has a value of signifkan < 0.005. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 5 publications
0
8
1
4
Order By: Relevance
“…The research on the correlation between workload and job performance is contradictory. Several researchers found that workload negatively and insignificantly impacts employee job performance [21,22]. Others asserted that the highest performance occurs when the workload is moderate and that there is a positive correlation between workload and performance [19,20].…”
Section: Workload and Employee Job Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The research on the correlation between workload and job performance is contradictory. Several researchers found that workload negatively and insignificantly impacts employee job performance [21,22]. Others asserted that the highest performance occurs when the workload is moderate and that there is a positive correlation between workload and performance [19,20].…”
Section: Workload and Employee Job Performancementioning
confidence: 99%
“…None of these studies assessed the influence of supervisor work-life support on workload, work autonomy (as mediators) and job performance. In addition, further examination of previously published studies reveals conflicting findings in terms of the consequences of workload on job performance [19][20][21][22]. The empirical research relevant to the association between work autonomy and performance is also inconclusive in its conclusions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Jadi dapat disimpulkan bahwa beban kerja di Hotel Rangkayo Basa Padang masih tinggi. Berdasarkan penjelasan diatas, diharapkan dengan hasil penelitian ini bisa memberikan representasi dan masukan bagi Hotel Rangkayo Basa untuk mempertimbangkan kembali beban kerja yang diberikan kepada karyawannya, karena dengan beban kerja yang tinggi tentunya dapat mempengaruhi kinerja karyawan menjadi kurang maksimal [12].…”
Section: B Pembahasan 1 Beban Kerjaunclassified
“…Excessive workload by deadline for work or use up human resources. The workload cannot always be in full control of the total workload, but we can overcome the effect and take some preventive actions [5]. The level of loading that is too high allows the use of excessive energy and over stress occurs, on the other hand, the intensity of the loading is too low to allow boredom and boredom or under stress.…”
Section: Workloadmentioning
confidence: 99%